Adopting coffee to climate change: arabica rootstocks enhance physiological performance of robusta under water deficit - Patil, Somashekhargouda; Yashaswini, K. P.; Yashasvi, H. R.; Devasia, Jeena; Govindappa, M.; Babou, C.; Senthilkumar, M. (Frontiers in Climate, 2026)
IntroductionDrought stress is a critical limitation to robusta coffee (Coffea canephora) cultivation, particularly under prolonged dry seasons and increasing climate variability. Grafting robusta onto arabica (Coffea arabica) rootstocks is a promising strategy to enhance physiological performance under water-limited conditions.MethodsA three-year nursery study (2020–2023) was conducted at the Central Coffee Research Institute, Karnataka, India, to evaluate the drought response of two robusta scions (S.274 and C×R) grafted onto four tetraploid arabica rootstocks (Sln.6, Sln.9, S.4595 and Sln.5B). The experiment followed a randomized block design with three replications. Physiological and biochemical traits were assessed at before stress, at incipient wilting (9.4% soil moisture) (at stress) and 15 days after rewatering (after alleviation of stress).ResultsThe combination S.4595/C×R exhibited the lowest reduction in net photosynthesis (−7.7%) under stress and highest post-stress recovery. Sln.6/C×R and Sln.9/S.274 also performed well, while Sln.5B/C×R maintained stable stomatal conductance and full recovery. S.4595/C×R and Sln.5B/C×R showed minimal decline in intercellular CO₂, high relative water content (79.63%), and epicuticular wax deposition (29.90 µg/cm²), indicating enhanced water retention. These grafts also retained higher chlorophyll a and b content and demonstrated superior intrinsic water use efficiency.DiscussionArabica-rooted grafts, particularly S.4595/C×R, Sln.5B/C×R and Sln.6/C×R, significantly enhanced physiological tolerance to drought. These combinations offer promising options for developing climate-resilient coffee systems through rootstock-scion interactions, especially under increasing moisture stress scenarios.